Територіальна диференціація показників ефективності природно-заповідної мережі Волинської області - Павловська, Тетяна Сергіївна; Рудик, Олександр Володимирович; Воробей, Анастасія Василівна; Pavlovska, Tetiana S.; Rudyk, Oleksandr V.; Vorobei, Anastasiia V. (Східноєвропейський національний університет імені Лесі Українки, 2015)
Для оцінки геопросторових особливостей ефективності мережі природно-заповідного фонду (ПЗФ) Волинської області проаналізовано кількість та площу природно-заповідних територій (ПЗТ), щільність ПЗТ, коефіцієнт заповідності території, коефіцієнт розчленованості (інсуляризованості) ПЗФ в розрізі адміністративних одиниць, річкових басейнів, ландшафтних районів. Аналізовані показники картографічно відображені із застосування ГІС-технологій, що розширює можливості подальшого використання результатів даного дослідження у вирішенні наукових і прикладних завдань.

The article highlights the results of geospatial peculiarities’ research in terms of conservation area quality in Volyn region. The research of natural reserves’ functional properties and the high level of excellence evaluation of its functioning are necessary for determination the priority trend in the development of protected areas in the region. To assess the nature reserve effectiveness of Volyn region the following issues are analyzed: the number and area of protected areas, the density of protected areas, the conservation area rate, the rate of compartmentalization (insularization) of nature reserve fund in terms of administrative units (16 administrative regions), catchment area (Bug River, Pripyat, Vyzhivka, Turiya, Stokhid, Styr), natural (landscape) areas which are allocated to the region by K. I. Herenchuk (Verhnopryp'yatsk, Shatsk, Kovel, Lyuboml, Manevychi, Turiysk, Tsuman , Kolki, Lutsk, Ivanychi, Gorokhiv). Analyzed indicators are cartographically reflected with the application of GIS technology that enhances the further use of the results of this study in solving scientific and applied problems.
Territorial differentiation of natural reserve’s efficiency indicators in Volyn region
Keywords: природно-заповідні території; природно-заповідний фонд; коефіцієнт заповідності; коефіцієнт інсуляризованості; щільність об’єктів ПЗФ; natural protected areas; nature reserve fund; conservation area rate; the rate of insularization; density of protected areas